Musiklernwelten erkennen und gestalten Eine qualitative Studie über Musikschularbeit in Österreich - Ardila-Mantilla, Natalia (LIT Verlag GmbH & Co. KG, 2016)
The research project Recognizing, Acknowledging and Designing Music Learning Worlds studied the educational practices and the music education principles of music school teachers in Austria. The project was designed as a qualitative comparative study, based on the Grounded Theory method, and using formal/informal (music) learning as a sensitizing concept. The resulting grounded theory defines the work of teachers in music schools as the constant process of recognizing, acknowledging and designing music learning worlds.